What is essential?: Understanding community resilience and public libraries in the United States during disasters. Issue 1 (22nd October 2020) - Patin, Beth
Abstract: Hurricane Katrina, the 4/27/2011 Tornadoes, the Oso Mudslide, and even more recently, the Coronavirus Pandemic, all demonstrated the devastating experience of disaster. While each of these extreme events varied in scope, size, and degree of disruption, each overwhelmed local authorities necessitating state and federal assistance. Prevention of disasters is ideal, but not practical. Preferably, the emphasis is placed on resilience or a community's ability to bounce back. Public libraries are considered trusted pillars in their community, posing them to provide critical information in the face of extreme challenges. This work explores community resilience and how public libraries in the United States, as Federal Emergency Management Agency (FEMA)‐designated essential community organizations, enhance community resilience. American Library Association Policy already recognizes the role libraries should play, and more recently, FEMA recognized libraries as "essential community organizations, " tasking them with the responsibility of fulfilling critical information needs in the case of a disaster. However, this designation was made without a clear understanding of how libraries should support their communities, leading to confusion during the United States' response to Covid19. This work identifies a gap between the perspectives of the librarians and disaster response agents and suggests methods for closing this gap.